ANALISIS SISTEM PEMBELAJARAN BERBASIS TEKNOLOGI DI ERA DIGITAL DALAM PENINGKATAN KREATIVITAS MURID - Nurul Hikmah Fauziyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the planning of digital technology-based learning systems in Indonesia. The method used is literature review. In this literature review research, books and national journals are used which have been summarized and analyzed. The results show that the role of technology-based learning systems in the digital era is crucial in the teaching and learning process. The utilization of technology aims to facilitate the understanding of material by students and turn abstract concepts into something more concrete. The use of teaching materials in the classroom has the potential to increase effectiveness, maximize results, and optimize the learning process. With the conclusion that the improvement of teachers in utilizing digital technology can have a considerable positive impact on learning.